Ultra-High Dose Rate Electron Beam Dosimetry Using Ag Nanoparticle-Enhanced nPAG and NIBMAGAT Gels - Mantvydas Merkis; Akvile Slektaite-Kisone; Marius Burkanas; Aleksandras Cicinas; Mindaugas Dziugelis; Vaidas Klimkevicius; Diana Adliene; Jonas Venius (Gels)
FLASH radiation therapy is an emerging technique that provides several advantages over conventional radiotherapy. By delivering ultra-high dose rate radiation, the damage to healthy tissues surrounding the treatment area is minimized, treatment time is reduced and treatment outcomes of radioresistant tumors are improved. Despite its promising potential, FLASH radiation therapy remains relatively understudied, particularly in the field of dosimetry. Polymer gel dosimetry is a promising technique for verifying FLASH radiation therapy because it enables volumetric dose distribution measurements with high spatial accuracy. This study investigates the applicability of two commonly used polymer gel dosimeters, nPAG and NIBMAGAT, enhanced with nanoparticles, in ultra-high dose rate radiation therapy. The results indicate that NIBMAGAT gel, enriched with Ag nanoparticles, outperforms nPAG. NIBMAGAT gel exhibits less saturation at high doses, maintains dose rate independence and offers comparable sensitivity to nPAG formulation.